1960
DOI: 10.1038/187245a0
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin in the Neurohypophysis of the Laying Hen

Abstract: We have found that the concentration of citric acid in the isthmus is not altered in birds injected with fluoroacetate, and the enzymes of the Krebs cycle which seem most likely to be implicated in the high citric acid content of this region are under invel!ltigation.The tubular region of the uterus adjacent to the isthmus, the isthmo-uterine junction•, is considerably richer in calcium and citric acid than the thick muscular region where the main process of shell calcification occurs, and this may be due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1963
1963
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Munsick et al (1960) has shown that the concentration of AVT in the fowl neurohypophysis is 10 times that of oxytocin and Tanaka and Nakajo (1960;1962) reported a decrease in the AVT content of the neurohypophysis which coincided with oviposition. Douglas and Sturkie (1964) and Lin (1966, 1967) measured AVT in the blood of laying hens and found that the activity of the hormone increased markedly during oviposition.…”
Section: Introductionmentioning
confidence: 96%
“…Munsick et al (1960) has shown that the concentration of AVT in the fowl neurohypophysis is 10 times that of oxytocin and Tanaka and Nakajo (1960;1962) reported a decrease in the AVT content of the neurohypophysis which coincided with oviposition. Douglas and Sturkie (1964) and Lin (1966, 1967) measured AVT in the blood of laying hens and found that the activity of the hormone increased markedly during oviposition.…”
Section: Introductionmentioning
confidence: 96%
“…Electrical lesions or stimulations of the hen hypothalamus (18,19), where neurons concerning the release of neurohypophysial hormones are located, delay or induce oviposition, suggesting that oviposition is controlled by the central nervous system through the release of AVT. At the time of oviposition, AVT is acutely released from the neural lobe of the pituitary, as evidenced by a decrease in the AVT content in the neural lobe (20,21) and a remarkable increase in the plasma AVT concentration (12,(22)(23)(24). However, whether AVT is the trigger for the initiation of contraction of the uterus, resulting in oviposition, is unknown.…”
mentioning
confidence: 99%
“…The contraction of uterine muscle is caused by AVT (Munsick et al, 1960;Rzasa, 1972), presumably through binding to its receptor existing in the uterus (Takahashi et al, 1992;1994a), and oviposition is induced (Rzasa and Ewy, 1970;Taka-hashi and Kawashima, 2003;2008;Takahashi et al, 2004). The concentration of AVT has been detected to decrease in the neurohypophysis (Tanaka and Nakajo, 1960;1962) and the dramatic increase in blood (Douglas and Sturkie, 1964;Tanaka et al, 1984;Rice et al, 1985;Shimada et al, 1986;Koike et al, 1988;Takahashi et al, 1994a;Takahashi and Kawashima, 2008) just after oviposition. The blood concentration of AVT has been reported to be increased by estrogen (Takahashi et al, 1994b) and prostaglandin F 2α (PGF 2α ; Takahashi and Kawashima, 2009a).…”
Section: Introductionmentioning
confidence: 93%